2020
DOI: 10.1186/s13750-020-0184-0
|View full text |Cite
|
Sign up to set email alerts
|

What are the relative risks of mortality and injury for fish during downstream passage at hydroelectric dams in temperate regions? A systematic review

Abstract: Background: Fish injury and mortality resulting from entrainment and/or impingement during downstream passage over/through hydropower infrastructure has the potential to cause negative effects on fish populations. The primary goal of this systematic review was to address two research questions: (1) What are the consequences of hydroelectric dam fish entrainment and impingement on freshwater fish productivity in temperate regions?; (2) To what extent do various factors like site type, intervention type, and lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 60 publications
3
61
0
1
Order By: Relevance
“…Although fish entering the intake towers are avoiding the turbines and thus the associated direct mortality attributed to turbine passage (Pracheil et al 2016; Algera et al 2020), stranding in the surge towers is also potentially hazardous. Anecdotally, during the study dead fish (of various species including Rainbow Trout and Lake Whitefish) were observed and a considerable number of free‐swimming fish had fungal infections (see the Supplementary Material).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although fish entering the intake towers are avoiding the turbines and thus the associated direct mortality attributed to turbine passage (Pracheil et al 2016; Algera et al 2020), stranding in the surge towers is also potentially hazardous. Anecdotally, during the study dead fish (of various species including Rainbow Trout and Lake Whitefish) were observed and a considerable number of free‐swimming fish had fungal infections (see the Supplementary Material).…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple downstream passage routes for fish at hydropower facilities, including turbines, spillways, and a variety of bypasses (OTA 1995; Katopodis and Williams 2012;). In facilities lacking passage infrastructure, fish passage through turbines is common and can result in mortality and/or injury (Coutant and Whitney 2000; Pracheil et al 2016; Algera et al 2020). Turbine intake towers, designed to retain water for safety and maintenance purposes, provide no purpose‐built fish passage (aside from being flushed through turbines) and can strand entrained fish for considerable periods of time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream movement is impaired because drifting larvae, and even adult fish, are unable to find their way through the standing water of the impoundment to locate the outlet (Pelicice et al, 2015). Moreover, adult and juvenile fish which attempt to pass through hydropower infrastructure experience severe mortality from shear forces, physical strikes from turbine blades, and barotrauma or changes in barometric pressure (Algera et al, 2020).…”
Section: Impacts Of Hydropower Dams On the Mekongmentioning
confidence: 99%
“…There are multiple downstream passage routes for fish at hydropower facilities including turbines, spillways, and a variety of bypasses (OTA 1995;Katopodis and Williams 2012). In facilities lacking passage infrastructure, fish passage through turbines is common and can result in mortality and/or injury (Coutant and Whitney 2000;Pracheil et al 2016;Algera et al 2020). Turbine intake towers, designed to retain water for safety and maintenance purposes, provide no purpose-built fish passage (aside from being flushed through turbines) and can strand entrained fish for considerable periods of time.…”
Section: Introductionmentioning
confidence: 99%